Long‐Term Observations of Galactic Cosmic Ray LET Spectra in Lunar Orbit by LRO/CRaTER. Issue 12 (2nd December 2020) - Looper, M. D.; Mazur, J. E.; Blake, J. B.; Spence, H. E.; Schwadron, N. A.; Wilson, J. K.; Jordan, A. P.; Zeitlin, C.; Case, A. W.; Kasper, J. C.; Townsend, L. W.; Stubbs, T. J.
Abstract: The Cosmic Ray Telescope for the Effects of Radiation (CRaTER) has been orbiting the Moon since 2009 aboard the Lunar Reconnaissance Orbiter (LRO). From this vantage point, it samples the interplanetary energetic particle population outside the shielding of the Earth's magnetosphere. We report the sensor's observations of galactic cosmic rays (GCRs) over a complete solar activity cycle. CRaTER is designed primarily to measure not the spectra of GCR particles outside the sensor but rather their effects on matter, and in particular, it measures the linear energy transfer (LET) or energy‐deposit spectrum in its silicon detectors. We have used the Geant4 radiation‐transport code to devise a background‐rejection algorithm to improve these measurements of LET under 9.9 g/cm 2 of shielding, and the resulting observations show the changing radiation effects of GCRs as their intensity and spectrum vary with solar modulation. As of 2020 this intensity, after declining during solar maximum activity, has recovered to a level that exceeds by a few percent the historically high values seen during the deep solar minimum at the start of the LRO mission in 2009. Plain Language Summary: Energetic particle radiation consists of fast‐moving atomic fragments traveling in space. The particles with the highest energy, called cosmic rays, can penetrate even thick shielding and deposit their energy into astronauts or electronics, causing radiation damage. A sensor aboard the Lunar Reconnaissance Orbiter satellite has been measuring cosmic rays in orbit around the Moon since 2009, monitoring the varying intensity of their radiation effects, and this paper reports improvements we have made to these measurements. The Sun's output of energetic particles, magnetic fields, and so forth varies on an 11‐year cycle, and this activity affects the intensity of cosmic rays coming into the solar system. Our measurements of cosmic ray radiation effects show that, after a decline during the middle of the solar activity cycle, as of 2020 their intensity has risen back to exceed the historically high levels seen at the start of the mission. Key Points: The Cosmic Ray Telescope for the Effects of Radiation has measured galactic cosmic rays at the Moon over a full solar activity cycle We have used the Geant4 radiation‐transport code to improve background rejection in measurements of Linear Energy Transfer spectra The intensity of galactic cosmic rays, as of early 2020, has recovered and now slightly exceeds the historically high levels of 2009